Accelerate Implementation of the WHO Global Code of Practice on International Recruitment of Health Personnel: Experiences From the South East Asia Region; Comment on "Relevance and Effectiveness of the WHO Global Code Practice on the International Recruitment of Health Personnel - Ethical and Systems Perspectives" - Viroj Tangcharoensathien; Phyllida Travis (Kerman University of Medical Sciences, 2016)
Strengthening the health workforce and universal health coverage (UHC) are among key targets in the heathrelated Sustainable Development Goals (SDGs) to be committed by the United Nations (UN) Member States in September 2015. The health workforce, the backbone of health systems, contributes to functioning delivery systems. Equitable distribution of functioning services is indispensable to achieve one of the UHC goals of equitable access. This commentary argues the World Health Organization (WHO) Global Code of Practice on International Recruitment of Health Personnel is relevant to the countries in the South East Asia Region (SEAR) as there is a significant outflow of health workers from several countries and a significant inflow in a few, increased demand for health workforce in high- and middle-income countries, and slow progress in addressing the "push factors." Awareness and implementation of the Code in the first report in 2012 was low but significantly improved in the second report in 2015. An inter-country workshop in 2015 convened by WHO SEAR to review progress in implementation of the Code was an opportunity for countries to share lessons on policy implementation, on retention of health workers, scaling up health professional education and managing in and out migration. The meeting noted that capturing outmigration of health personnel, which is notoriously difficult for source countries, is possible where there is an active recruitment management through government to government (G to G) contracts or licensing the recruiters and mandatory reporting requirement by them. According to the 2015 second report on the Code, the size and profile of outflow health workers from SEAR source countries is being captured and now also increasingly being shared by destination country professional councils. This is critical information to foster policy action and implementation of the Code in the Region.